Isotopic ratios of uranium and caesium in spherical radioactive caesium-bearing microparticles derived from the Fukushima Dai-ichi Nuclear Power Plant - Yuichi Kurihara (Nature Portfolio, 2020)
Abstract Spherical radioactive caesium (Cs)-bearing microparticles (CsMPs) were emitted during the Fukushima Dai-ichi Nuclear Power Plant (FDNPP) accident in March, 2011. The emission source (timing) and formation process of these particles remain unclear. In this study, the isotopic ratios of uranium (235U and 238U) and caesium (133Cs, 134Cs, 135Cs, and 137Cs) isotopes in the five spherical CsMPs (ca. 2 μm in size) sampled at 50 km west of the FDNPP were determined using secondary ion mass spectrometry and laser ablation-ICPMS, respectively. Results showed that the 235U/238U ratios of CsMPs were homogeneous (1.93 ± 0.03, N = 4) and close to those estimated for the fuel cores in units 2 and 3, and that the Cs isotopic ratios of CsMP were identical to those of units 2 and 3. These results indicated that U and Cs in the spherical CsMPs originated exclusively from the fuel melt in the reactors. Based on a thorough review of literatures related to the detailed atmospheric releases of radionuclides, the flow of plumes from the FDNPP reactor units during the accident and the U and Cs isotopic ratio results in this study, we hereby suggest that the spherical CsMPs originate only from the fuel in unit 2 on the night of 14 March to the morning of 15 March. The variation range of the analysed 235U/238U isotopic ratios for the four spherical particles was extremely narrow. Thus, U may have been homogenised in the source through the formation of fuel melt, which ultimately evaporating and taken into CsMPs in the reactor and was released from the unit 2.